2021
DOI: 10.1136/bcr-2021-243888
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome in an adult following the SARS-CoV-2 vaccine (MIS-V)

Abstract: SARS-CoV-2 vaccine roll-out has been successful in the UK and other parts of the world; however, there are increasing concerns about adverse events. A 44-year-old woman presented to a UK hospital with left upper arm pain at the vaccine site a couple of days after receiving the Pfizer-BioNTech mRNA vaccine, which progressed to fever, diarrhoea and abdominal pain over the next few days. She had an erythematous rash on the chest with subcutaneous oedema. Her C reactive protein was 539 mg/L, white cell count of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 25 publications
8
109
0
Order By: Relevance
“…The existing data regarding MIS-A suggest a similar convalescent response in adults [ 15 , 16 , 17 , 18 ]. Nevertheless, reports of a multisystem inflammatory syndrome after vaccination (MIS-V) in individuals who had received immunization after recovering from mild COVID-19, or perhaps non-neutralizing antibodies from other coronaviruses, suggest an alternative pathogenesis involving antibody enhancement that leads to the hyper-inflammatory syndrome [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existing data regarding MIS-A suggest a similar convalescent response in adults [ 15 , 16 , 17 , 18 ]. Nevertheless, reports of a multisystem inflammatory syndrome after vaccination (MIS-V) in individuals who had received immunization after recovering from mild COVID-19, or perhaps non-neutralizing antibodies from other coronaviruses, suggest an alternative pathogenesis involving antibody enhancement that leads to the hyper-inflammatory syndrome [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 1 case of MIS after the Pfizer‐BioNTech mRNA vaccine has been described in a 44‐year‐old woman without a previous SARS‐CoV‐2 infection. 3 …”
mentioning
confidence: 99%
“…MIS-C has been associated with heart failure in some cases ( 127 ). A small number of case studies have identified presentations similar to MIS-C in adults associated with SARS-CoV-2 ( 128 131 ). However, not all cases of severe COVID-19 in children are characterizable as MIS-C. A recent study ( 132 ) described demographic and clinical variables associated with MIS-C in comparison with non-MIS-C severe acute COVID-19 in young people in the United States.…”
Section: Clinical Presentation Of Covid-19mentioning
confidence: 99%